Malaysian trainee teachers’ readiness towards virtual learning: a Q Methodology / Tan Tong Hock and Ahmad Fauzi Mohd Ayub - Tan, Tong Hock; Mohd Ayub, Ahmad Fauzi (Universiti Teknologi MARA, 2024)
The COVID-19 pandemic has brought a major impact to over 1.2 billion children across 186 nations due to the school closures to manage the spread of the disease. Yet, despite this, classroom teaching and learning had to continue to keep the education system afloat, resulting in the shift to online or virtual learning that had also impacted the worldwide education market. Virtual learning has become linked to formal education, as well as the interactions among teachers, students, and educational institutions. However, virtual learning faces challenges such as limited internet access, students’ readiness, and unproven effectiveness. Hence, this study utilised the Q-Methodology to investigate the knowledge level of Malaysia higher education trainee teachers on virtual learning, the attitude of trainee teachers towards virtual learning, and their readiness towards virtual learning after the shift to the endemic stage. The respondents were 54 trainee teachers from the Malaysian Higher Education Teacher Institution. The results showed that most trainee teachers had a good understanding of virtual learning, were prepared to apply the new standard medium of digital technology, and had an optimistic attitude. However, a small group was still not ready for the new normal. Hence, the findings suggest that lecturers faced a significant challenge and needed to exert more effort to design lessons that can attract trainee teachers to prepare for virtual learning.